SRI‐42127, a novel small molecule inhibitor of the RNA regulator HuR, potently attenuates glial activation in a model of lipopolysaccharide‐induced neuroinflammation. Issue 1 (17th September 2021) - Chellappan, Rajeshwari; Guha, Abhishek; Si, Ying; Kwan, Thaddaeus; Nabors, Louis B.; Filippova, Natalia; Yang, Xiuhua; Myneni, Anish S.; Meesala, Shriya; Harms, Ashley S.; King, Peter H.
Abstract: Glial activation with the production of pro‐inflammatory mediators is a major driver of disease progression in neurological processes ranging from acute traumatic injury to chronic neurodegenerative diseases such as amyotrophic lateral sclerosis and Alzheimer's disease. Posttranscriptional regulation is a major gateway for glial activation as many mRNAs encoding pro‐inflammatory mediators contain adenine‐ and uridine‐rich elements (ARE) in the 3′ untranslated region which govern their expression. We have previously shown that HuR, an RNA regulator that binds to AREs, plays a major positive role in regulating inflammatory cytokine production in glia. HuR is predominantly nuclear in localization but translocates to the cytoplasm to exert a positive regulatory effect on RNA stability and translational efficiency. Homodimerization of HuR is necessary for translocation and we have developed a small molecule inhibitor, SRI‐42127, that blocks this process. Here we show that SRI‐42127 suppressed HuR translocation in LPS‐activated glia in vitro and in vivo and significantly attenuated the production of pro‐inflammatory mediators including IL1β, IL‐6, TNF‐α, iNOS, CXCL1, and CCL2. Cytokines typically associated with anti‐inflammatory effects including TGF‐β1, IL‐10, YM1, and Arg1 were either unaffected or minimally affected. SRI‐42127 suppressed microglial activation in vivo and attenuated the recruitment/chemotaxis of neutrophils and monocytes. RNA kinetic studies and luciferase studies indicated that SRI‐42127 has inhibitory effects both on mRNA stability and gene promoter activation. In summary, our findings underscore HuR's critical role in promoting glial activation and the potential for SRI‐42127 and other HuR inhibitors for treating neurological diseases driven by this activation. Main Points: HuR promotes expression of pro‐inflammatory cytokines in LPS‐activated glial cells. SRI‐42127 inhibits HuR multimerization and thereby impairs downstream HuR functions including shuttling, mRNA stability, translational efficiency, and gene promoter regulation. SRI‐42127 suppresses pro‐inflammatory cytokines in LPS‐activated glial cells.